Signscape : signal transduction networks visualization application - Tan, Huiyi (2014)
In a fast moving society, we are constantly on the move and we rely heavily on the Internet to retrieve relevant information. The advancement in technology has definitely benefitted many – such as the area of biological research. New grounds have been broken and the focus is now shifting to target-based drug discovery. As we live in a world of uncertainties, we need to leverage on existing technology to prepare ourselves for the future. Thus, researchers need to understand the functions of each protein in order to develop new products. Signal transduction, which can be defined as the elemental component that oversees the cell function, relies on signaling pathways which are usually visualized as networks. There are not many tools available that can provide this level of visualization. Therefore, for my final year project, I will introduce SignScape, a web-based application that I have built using an open-source graph library to visualize the network topology of signal transduction. Based on the current work in MATLAB, I will map existing algorithms that are used for visualization in MATLAB to SignScape, in particular Pearson product-moment correlation coefficient and partial least squares regression using SIMPLS algorithm. Visual aspects and performance comparison will be done between SignScape and current work in MATLAB to show why my proposed solution is a more viable one.